MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN INKLUSI PADA PAUD INKLUSI SE KOTA PEKANBARU - Oktavianti, Vina; Zulkifli N, Zulkifli N; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study adopted the management and infrastructure of inclusive educationespecially on its process such as planning, supplying, inventorization, maintaining and banning. The aim of this study to know how is the management and infrastructure of inclusive education in Early Childhood Education (ECD) in Pekanbaru. The subject of this study werethree inclusive Early Childhood Education principals. This study applied qualitative approachand the data were gathered by collecting information from interview, observation and documentation. The data were analyzed using qualitative analysis included the data reduction, presentation of data, conclusion and verification. This study used triangulation method in order to gather information by using different methods to match some collected data were gathered from interview, observation and documentation. According from result of the interview showed management and infrastructure of inclusive education in Early Childhood Education is quite good. Every each of inclusive Early Childhood Education institution has been implementing the planning, supplying, inventorization, maintaining and banning properly based on the set of standard.Key Word: Education infrastructure management, inclusive education